Understanding and Pronunciation of Speaking and Making Speeches Using English in Junior High School Children - Daniel Setiawan Zamasi; Hia, Maria Putri Cantika; Waruwu, Yaredi (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2024)
This journal delves into the linguistic prowess of junior high school children in English speech construction. Through quantitative methods utilizing structured questionnaires, the study evaluates the proficiency of students in speaking and delivering English speeches. Findings reveal a spectrum of abilities: from confusion and difficulty among some students to proficient articulation and comprehension among others. Notably, a significant portion of students exhibit self-directed learning through mediums like online gaming, contributing to their language acquisition. The study underscores the diverse pathways through which junior high school children acquire English proficiency, with approximately 60% - 70% demonstrating the ability to construct and deliver English speeches effectively, showcasing varied speaking styles.